(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
Mesenchymal stem cells therapy opened new perspective in the management of osteoarthritis. This study focuses on a randomized controlled trial pilot on 10 patients of osteoarthritis knees to evaluate the intra-articular injections of mesenchymal stem cells could improve the symptoms, functional limitation and regeneration of cartilage. Mesenchymal stem cells were obtained from peripheral blood after mobilization of blood cell with granulocyte colony stimulating factor by apheresis machine. Single dose of mesenchymal stem cells were injected into the affected joints, WOMAC questionnaires scale used to record pre and post-treatment improvement, cartilage thickness measured by high frequency ultrasonogram. Four patients were having Grade II and six were having Grade III osteoarthritis. Kellgren-Lawrence scale was used for radiological grading. Pain score were decreased at the end of 24th weeks from 14.8 ± 2.2 to 4.1 ± 1.3, Stiffness score decreased from 5.8 ± 0.6 to 0.7 ± 0.6, Physical function limitation score reduced from 46.7 ± 6.5 to 20.3 ± 2.5. There was minor improvement of range of motion and cartilage thickness changes. This study demonstrates that mesenchymal stem cells injections improves all parameters of knee osteoarthritis and minimal regeneration of damaged cartilage.